2008
DOI: 10.3354/meps07458
|View full text |Cite
|
Sign up to set email alerts
|

Plankton trophic structure and particulate organic carbon production during a coastal downwelling-upwelling cycle

Abstract: ) indicated the establishment of a herbivorous food web structure. Particulate organic carbon (POC) production was mainly due to phytoplankton (98%) and did not differ between periods. However, the observed variability in plankton trophic interactions should affect the magnitude of POC export from this dynamic system. KEY WORDS: Food webs · Carbon fluxes · Bacterioplankton · Phytoplankton · Zooplankton · Cabo Frio · South Brazil Bight Resale or republication not permitted without written consent of the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 43 publications
1
33
0
2
Order By: Relevance
“…The strong association between SACW and mesozooplankton biomass confirm the importance of these intrusions to enhance local productivity (Metzler et al 1997, Saldanha-Corrêa andGianesella 2004), especially of herbivorous mesozooplankton (Guenther et al 2008), since we found typically herbivorous groups associated to intrusions (e.g. calanoids, including Temora spp.…”
Section: Mesozooplankton Temporal Patternssupporting
confidence: 87%
See 2 more Smart Citations
“…The strong association between SACW and mesozooplankton biomass confirm the importance of these intrusions to enhance local productivity (Metzler et al 1997, Saldanha-Corrêa andGianesella 2004), especially of herbivorous mesozooplankton (Guenther et al 2008), since we found typically herbivorous groups associated to intrusions (e.g. calanoids, including Temora spp.…”
Section: Mesozooplankton Temporal Patternssupporting
confidence: 87%
“…In a stratified water column with warmer surface temperature scenario, the surface water can be rapidly nutrient-depleted and the phytoplankton community is likely to be dominated by picoplankton and flagellates (Margalef 1997). On the other hand, under the SACW upwelling further north in Cabo Frio, when nutrients are injected in pulses, the phytoplankton community is largely dominated by diatoms (Guenther et al 2008). Therefore, although SACW bottom intrusions inject nutrients in the system, as in an upwelling event, this water mass rarely reaches the surface on the inner shelf off Ubatuba.…”
Section: Nbss and Size Structure Temporal Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…During such periods, oligotrophic waters dominate in the Cabo Frio area and the plankton community experiences extensive nutrient limitation (Valentin 1984). The system is then characterized by a microbial food web structure, whereby carbon produced by bacteria and small phytoplankton cells is channeled via flagellates and ciliates up to the mesozooplankton and higher trophic levels (Guenther et al 2008). Occasional development of large dinoflagellate cells -like Ceratium falcatiforme -during these periods might restrict carbon flow up the food web.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse pattern comes with the S-SW winds when cold fronts bring the oligotrophic TW back to the coast [49]. According [50] these processes have a direct impact on the quantity and composition of the plankton communities, shifting the trophic structure.…”
Section: Study Areamentioning
confidence: 99%